Heterogeneous photodegradation of orange G under the influence of added oxidising agents using TiO2 thin film - Md. Din, Mohd. Fadhil; Aris, Azmi; Salim, Mohd. Razman; Abu Bakar, Wan Azlee (Faculty of Civil Engineering, UTM, 2005)
This study examined the effect of added oxidising agents on the photocatalytic performance of immobilised TiO, thin film. Two oxidising agents were used, namely 02 and F1202 were used. Orange G (OG) was used as the model compound. The experiments were carried out batch-wise using a 200 ml photoreactor and UV light of wavelength 365 nm. It was observed that the addition of 02 and the peroxide significantly enhanced the photocatalytic process. Adding of pure 02 and 1mM H2O, has increased the degradation of 1 mM OG from 2% to 43% and 29%, respectively. Such addition has also improved the biodegradability (based on POD) of the dyestuff from 4 mgli to 24 mg1-1. While then increase in 02 concentration can improve the process, the correct dosage of peroxide required optimisation.